2014
DOI: 10.1002/cbin.10392
|View full text |Cite
|
Sign up to set email alerts
|

BH3‐only protein Bim is upregulated and mediates the apoptosis of cardiomyocytes under glucose and oxygen‐deprivation conditions

Abstract: Bim is a potent pro-apoptotic BH3-only Bcl-2 member. However, the expression of Bim and its role in cardiac injury induced by ischemia remain unclear. H9c2 cells were subjected to a glucose and oxygen-deprived (GOD) condition in vitro, mimicking ischemia environment in vivo. GOD treatment augmented the expression of Bim and induced the apoptosis of H9c2 cells. Silencing of Bim by RNAi significantly attenuated GOD-induced cytotoxicity, suppressed mitochondrial membrane potential △Ψm loss, inhibited caspase 3 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In agreement with our results, it was observed that Bim 10 transcription is repressed due to the kit mutation in human mast cells expressing the Kit D816V mutation, but when the proteasome is inhibited, Bim is upregulated and induces caspase-3-dependent apoptosis [41]. Apoptosis mediated by Bim protein has recently been reported under glucose and oxygen-deprivation conditions in cardiomyocytes [42] and cytokine deprivation in mouse mast cells [43]. Our results show that for the first time vitamin D agonists 1α,25(OH) 2 D 3 or TX 527 induce a change in the balance of pro and anti-apoptotic proteins in SVEC and vGPCR cells.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with our results, it was observed that Bim 10 transcription is repressed due to the kit mutation in human mast cells expressing the Kit D816V mutation, but when the proteasome is inhibited, Bim is upregulated and induces caspase-3-dependent apoptosis [41]. Apoptosis mediated by Bim protein has recently been reported under glucose and oxygen-deprivation conditions in cardiomyocytes [42] and cytokine deprivation in mouse mast cells [43]. Our results show that for the first time vitamin D agonists 1α,25(OH) 2 D 3 or TX 527 induce a change in the balance of pro and anti-apoptotic proteins in SVEC and vGPCR cells.…”
Section: Resultssupporting
confidence: 92%
“…Our findings indicate that FOXO1 may contribute to the induction of apoptosis in cardiomyocytes in response to CIH. Furthermore, under sustained conditions of CIH stress, FOXO1 induced expression of the pro-apoptosis gene, Bim, to trigger programmed death of cardiomyocytes [ 31 ]. The ability of FOXO1 to induce apoptosis at multiple steps has generated considerable interest, and efforts have been made to assess its roles in CIH-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that BCL2L11 is a dual-agent that regulates autophagy in drug resistance (Dai and Grant, 2015 ), and BCL2L11 is also involved in neural apoptosis in methylmalonic academia (Li et al, 2014 ). The anti-apoptotic BCL2 members have multiple domains; while the pro-apoptotic members of BCL2 family, including BCL2L11, are BH3-domain-only proteins (Mansha et al, 2013 ; Frank et al, 2015 ; Huang et al, 2015 ). Although the role of BCL2L11 has been reported in these biological processes, the information that BCL2L11 regulates cell growth and apoptosis in cancer, especially in gastrointestinal tumors, remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%